ANALYSIS OF COMMUNITY COMPLIANCE WITH THE COVID-19 HEALTH PROTOCOLS: A QUANTITATIVE ANALYTICAL APPROACH - Sukarsa, I Komang Gde; Gandhiadi, GK (PATTIMURA UNIVERSITY, 2023)
This study identifies the factors used in factor analysis that influence the compliance of the people of Bali Province to the COVID-19 health protocol. Based on the factor analysis results, the elimination of four variables from the initial 20 variables in the study because the low communality value was below 0.5. Thus, reducing the remaining 16 variables to six factors with a total variance of 74.8%. Six factors influenced Community compliance in Bali Province, namely someone who knows about the importance of health protocols (19,1%), trust in protocols (15,9%), someone infected with COVID-19 (12,2%), a sense of concern for themselves and their families (10,1%), government supervision and sanctions (9,3%), and the affordable price of masks (8,2%). Observing this study, the first factor that played a role in increasing adherence was knowledge about the importance of health care. There was a sense of trust in health protocols, and a less influential factor was the affordability of masks